Public health foundations concepts and practices - Andresen, Elena; Bouldin, Erin DeFries (Jossey-Bass, 2010)
"Foundations of Public Health is a concise yet comprehensive text that offers an excellent and engaging introduction to the field of public health. This important resource is an up-to-date introduction to the core concepts and the practices of public health. The book introduces public health in concept and its systems; the foundational tools of data, epidemiology, biostatistics, and key study designs; populations' issues including infectious disease, health behavior, and environmental health plus analytical tools of qualitative research and risk assessment; and how health services are formulated and delivered."--